Endless Revision Loop Syndrome: Fenomena Stres Berkepanjangan pada Mahasiswa Penyusun Tugas Akhir - Septi Gumiandari; Siti Fatimah Nur I'aly Hasanah (STAI DDI Kota Makassar, 2026)
The thesis completion process frequently traps students in repetitive and unpredictable revision cycles, triggering prolonged stress and impeding timely graduation. This study aims to: (1) explore students' subjective experiences in confronting repeated revisions; (2) identify the determinant factors causing this phenomenon; (3) understand the dynamics of chronic stress that develops; and (4) formulate a new psychological construct termed Endless Revision Loop Syndrome (ERLS). A qualitative phenomenological approach was employed, involving five university graduates recruited through purposive sampling and in-depth interviews. The findings reveal that all informants experienced feeling 'trapped' in repetitive draft revision cycles without a predictable endpoint, accompanied by frustration, stagnation, and a crisis of self-confidence stemming from inconsistent supervisory guidance. Determinant factors include supervisor inconsistency, institutional bureaucratic rigidity, limited access to primary references, and low student self-efficacy. Psychological stress progressed from mild cognitive load to chronic distress manifesting as psychosomatic health disorders, defensive procrastination, and social isolation. ERLS is constructed as a specific psychological distress condition triggered by the interaction between external barriers and internal vulnerability, forming a subjective belief that the thesis process has no clear termination point, yet can be disrupted through mental resilience, assertive communication, and social support. This study contributes theoretically by introducing a new nomenclature in academic stress discourse, with practical implications for institutions in designing more responsive and transparent supervisory systems